1980
DOI: 10.1055/s-2008-1056518
|View full text |Cite
|
Sign up to set email alerts
|

Wertigkeit der Computertomographie bei der Stadieneinteilung primärer Lymphknotenneoplasien

Abstract: Staging was undertaken in 118 patients with primary lymph node neoplasms; the sensitivity of computer tomography in the paraaortic region was 80%, that of lymphography 89%. Specificity of computer tomography was 93%, of lymphography 95%. In the iliac region, sensitivity was 81% (CT) and 90% (lymphography), and specificity was 90% (CT) and 97% (Lymphography). The value of computer tomography should, however, be stressed, since it can demonstrate lymph nodes not shown by lymphography, including those in the medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1980
1980
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Our results corresponded well with those of previous studies, which suggested an upper normal level of 314.5 cm 3 for the splenic volume (8) and for a splenic index of 480 cm 3 (1026). Our results showed good agreement with the results of a previous study by Strijk et al (11) who reported diagnostic accuracy of 91% using the criterion of the splenic index > 480 mL as indicative of splenic involvement in HD.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results corresponded well with those of previous studies, which suggested an upper normal level of 314.5 cm 3 for the splenic volume (8) and for a splenic index of 480 cm 3 (1026). Our results showed good agreement with the results of a previous study by Strijk et al (11) who reported diagnostic accuracy of 91% using the criterion of the splenic index > 480 mL as indicative of splenic involvement in HD.…”
Section: Discussionsupporting
confidence: 93%
“…They were requested to measure splenic width, thickness, and length for splenic index obtained by multiplying splenic width, thickness, and length, as previously described (1011). Maximal width and thickness at the splenic hilum were measured on axial images.…”
Section: Methodsmentioning
confidence: 99%
“…5 5~ splenic index (16). Thus an index of 480 as upper limit for normal size (13) corresponds to a weight of 265 g. Several other studies revealed that a splenic weight of more than 500 g consistently implied splenic involvement (8,10,17). It was calculated that weight determination using a weight of 500 g as threshold value would result, for the present series, in an accuracy of 77 per cent, a specificity of 100 per cent and a sensitivity of 72 per cent.…”
Section: Discussionmentioning
confidence: 81%
“…Organ involvement was noted, and spleen size was calculated in retrospect using the splenic index. The splenic index (14,24) is calculated by multiplying spleen length, width, and thickness. Spleen length is the sum of all slice thicknesses (and intervals if used) on which the spleen is seen.…”
Section: Resultsmentioning
confidence: 99%
“…Spleen width and thickness are the largest (straight) organ diameters from anterior to posterior border, and from internal to external surface, respectively. According to previous studies (14), an index of 480is used as the upper limit of normal. By definition, a higher index indicates splenomegaly, and may suggest histologic involvement with lymphoma (23,24).…”
Section: Resultsmentioning
confidence: 99%